Frame Building of President’s IKN Visit Controversy in Indonesian News Portals - Benni Handayani; Fitri Hardianti; Bi Shanshan (Fakultas Dakwah dan Komunikasi UIN Sunan Gunung Djati Bandung Sunan Gunung Djati Bandung, 2025)
This study analyzes the news coverage of President Joko Widodo’s official visit to IKN (Ibu Kota Nusantara), accompanied by influencers on July 28, 2024. This topic gained significant attention in numerous mass media. The researcher conducted a quantitative content analysis of 87 news articles from 10 national online news portals. News portals, news slant, and news sources are the variables to determine the most dominant news frame by referring to the five generic news frames by Semetko and Valkenburg, as an analysis framework. Findings reveal significant differences between news portals and news slant, as well as between news portals and news sources. Each confirmed by the Fisher-Freeman-Halton Exact Test (p <.001), indicating that each online news portal follows a distinct pattern in presenting news slant and selecting news sources to be quoted in its reporting. MANOVA results show that there are several media effects on five generic news frames. Especially on the conflict frame, recorded a significant effect from the three independent variables: news portal (p = .006), news sources (p = .001), and news slant (p = .001). Meanwhile, the responsibility frame was more affected by the news portal variable. The human-interest frame (p = .001) and the morality frame (p = .021) were more frequently observed in news articles that cited news sources from intellectuals and NGOs. However, the economic consequences frame was not significantly affected by the three variables in our analysis. This indicates that the economic aspects were not the main focus in the news. This finding confirms that the media tends to emphasize conflict in reporting on this issue.